Implementasi Media Spectrum Strategy Model Solo Art Market Untuk Meningkatkan Social Engagement - Vanel, Zon; Wijaya, Lina Sinatra; Dewi, Gracelia Audriana; Huwae, George Nicholas (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Solo Art Market (SAM) faces challenges in fostering social engagement in an increasingly competitive digital era. This study aims to evaluate the implementation of the Media Spectrum Strategy Model based on the PESO approach (Paid, Earned, Shared, Owned) in SAM’s communication strategy. Using a qualitative descriptive method, the research analyzes the effectiveness of various media types, including social media, websites, and third-party coverage. The findings reveal that the PESO strategy successfully enhances social engagement and strengthens SAM’s reputation. Paid media contributes to broader exposure through a new website, owned media like Instagram provides control over messaging, earned media builds credibility through positive press, and shared media facilitates direct, authentic interaction with the audience. These results suggest that media synergy within the PESO model is effective in fostering stronger relationships between art institutions and their communities. The implications of this study are expected to serve as a strategic reference for other art organizations seeking to enhance social engagement and audience loyalty in the digital age.